A combined effect of polybrominated diphenyl ether and aquaculture effluent on growth and antioxidative response of mangrove plants. (June 2018) - Farzana, Shazia; Tam, Nora Fung Yee
Abstract: Mangrove wetland receives nutrient-rich aquaculture effluent (AE) from nearby farming activities and polybrominated diphenyl ethers (PBDEs) from the production and usage of flame retardants. The effects of BDE-209 (the most common PBDE congener), AE and their combination on two true mangrove species, namely Kandelia obovata and Avicennia marina, were compared in a 6-month microcosm study. Results showed that K. obovata was more sensitive to these contaminants than A. marina, as reflected by its enhanced production of leaf superoxide (O2 −∗ ) by BDE-209 and root malondialdehyde (MDA) by the combined BDE-209 and AE treatment. The hormesis model showed that the combined effects of BDE-209 and AE on the production of MDA, O2 −∗ and catalase (CAT) activity in K. obovata and A. marina were antagonistic except root O2 −∗ in A. marina, but the effects on leaf superoxide dismutase (SOD) activity in K. obovata, and root SOD and peroxidase (POD) activities in A. marina were synergistic. The defense mechanisms differed between treatment and species. The activities of SOD and POD were the main mechanisms to defend K. obovata and A. marina against BDE-209, but CAT in K. obovata and POD in A. marina were more important in defending the combined BDE-209 and AE treatment. Highlights: Between two mangrove species, Avicennia was more tolerant to BDE-209 than Kandelia. Superoxide dismutase and peroxidase were the main defensive mechanisms against BDE-209. Aquaculture effluent (AE) increased plant biomass and alleviated BDE-209 toxicity. AE counteracted BDE effects on antioxidative enzymes and reduced oxidative stress. Combined effects of BDE-209 and AE on malondialdehyde in mangroves were antagonistic.